The Mediating Role of Teacher Identification in the Relationship Between Psychological Distress and Teacher Satisfaction During COVID-19. (July 2022) - Jackson, Kyle; Noordien, Zorina; Padmanabhanunni, Anita; Pretorius, Tyrone B.
The current study examines the potential mediating role of professional identification of school teachers in the relationship between psychological distress and teaching satisfaction. Professional identification is the extent to which an individual identifies with a professional group, including the values, beliefs, and commitment the individual has in relation to the professional group. Professional identification has been linked to negative work outcomes, such as job performance and turnover intentions, as well as to adverse mental health outcomes. In the context of education, professional identification is the extent to which teachers identify with the teaching profession. Participants (N = 355) were school teachers in South Africa who completed the Center for Epidemiological Depression Scale, the Beck Hopelessness Scale, the Professional Identification Scale, and the Teaching Satisfaction Scale. Structural equation analysis showed that professional identification plays a fully mediational role in the relationship between psychological distress and teaching satisfaction. Interventions that strengthen teachers' identification with the teaching profession should be considered a priority.